Changes in the Position of Mandibular Third Molars Following Extraction and Non-Extraction Orthodontic Treatments - Maryam Poosti; Mohammad Basafa; Mohsen Hosseini; Farnaz Parvizi (Mashhad University of Medical Sciences, 2013)
Introduction: Impaction of third molars can be associated with a number of sequelae, each requiring a different type of treatment. The purpose of this study was to assess the changes in the position of lower third molars following extraction and non-extraction orthodontic treatments. Methods: Pre- and post-treatment panoramic radiographs of 26 class I malocclusion patients (4 male and 22 female) who were treated on a non-extraction basis were compared with those of 30 class I malocclusion patients (5 male and 25 female) who received orthodontic treatment following the extraction of all first premolars. In each group, the lower third molar angulations and their distance from the lower border of the mandible were assessed. Results: Paired t-tests and independent t-tests detected significant changes in the position of the lower third molars in the extraction group. Both the left and right molars became more upright and their distance from the lower border of the mandible increased. Similar changes were only seen in the position of the right mandibular third molars in the non-extraction group. Conclusion: Tooth extractions can bring about favorable changes in the position of mandibular third molars and possibly reduce their incidence of impaction